A Sociolinguistics of Code Mixing and Code Switching Between English and Indonesian Language at STKIP PGRI Sidoarjo - Joko Slamet; Ninik; Sulistyaningsih (STKIP PGRI SIDOARJO, 2020)
This study was aimed to analyze Code Mixing and Code Switching between English and Indonesian Language Done by the Lecturer of Advance English Grammar Subject at the 5th Semester Students of STKIP PGRI Sidoarjo. The study was designed in the form of qualitative descriptive study. The subjects in this study were the lecturer in the 5th semester of students of STKIP PGRI Sidoarjo who teaches the Advance English Grammar subject. The data were collected by using the methods of recording and writing on note of what lecturer said in teaching learning process, then collected it and classified based on grammatical aspect of code mixing, code switching, sociolinguistic aspect, and the function (phatic function) of code mixing and code switching. A grammatical focused on the structural aspect of code mixing and code switching. While, a sociolinguistic approach was concerned with the role of social factors of code mixing and code switching. The result of this research showed that the grammatical aspect of code mixing and code switching are extra-sentential/tag mixing and switching, inter-sentential mixing and switching, and intra word of code mixing and code switching. Sociolinguistic aspects of code switching are situational and metaphorical switching. The functions of code switching were referential function, directive function, phatic function and metalinguistic function. But this study only focused on phatic function to clarify or emphasize a message. The achievement of this research can be used to make easier in teaching foreign language and can be used as additional source and also can develop code mixing and code switching field in the next research.